The EU's regional trade agreements: How the EU addresses challenges related to digital transformation - Magdalena Slok-Wodkowska; Joanna Mazur (International Journal of Management and Economics, 2021)
The objective of this paper is to provide insight into the regulatory solutions that refer to the electronic commerce (e-commerce) adopted in the regional trade agreements (RTAs) of the European Union. Our goal is to compare these regulatory measures with the obstacles indicated in the literature as key issues hampering international digital trade. We provide a formal-dogmatic analysis of all of the newly adopted RTAs. The findings resulting from this analysis indicate that even though the regulatory dimension of global economic trade attempts to somehow address the issues resulting from the specific characteristics of the digital economy, the process is still in its infancy. The majority of provisions do not consider the key problems that impede international digital trade. The originality of our work results from its focus on the most recent RTAs, the analysis of which is hardly present in the scholarship.
Keywords: F1; K2; O31; 650; digital trade; electronic commerce; European Union; regional trade agreements